The challenge of plastics in a circular perspective - Preka, Rovena; Fiorentino, Gabriella; De Carolis, Roberta; Barberio, Grazia (Frontiers in Sustainable Cities, 2022)
Although plastic is a very important material in our economy and lifestyle, we need to deal with its pervasive impact and the huge amount of plastic waste produced, especially in the urban context. In Italy, the production of plastic waste is about 4.8 million tonnes with a share of 31.4% sent for recycling, 32.8% sent to Waste to Energy facilities and 35.8% sent to landfill. The negative effects of plastic waste have to be mitigated by means of prevention and other measures aimed at a transition to sustainable production and consumption patterns. The presented perspective takes advantage of the work done in the framework of the Italian Circular Economy Stakeholders Platform (ICESP) and identifies regulatory and technical criticalities in the sector, while defining strategic actions to be implemented along the entire value chain of plastics in the short, medium and long term perspective, with the aim of outlining possible mitigation solutions. From the snapshot of the ongoing advancement of the circular economy in the plastic sector, within the Italian urban context, suggestions can be gained for a strategy based on a systemic life cycle approach.